The new hype in the e-commerce industry: A case study in Sweden to investigate challenges perceived by software development teams - Hakobyan,Hasmik; Murugesan,Narthana (2023)
The growing number of users and the changes in customer behaviour over the last few years caused new hype in the e-commerce industry. This imposed pressure resulted in some technical disruptions in those systems. Software development teams responsible for creating and maintaining these systems, in their turn, were affected by the sudden shift to remote work. The current study aims to investigate specific challenges of the e-commerce systems, including issues connected to the software application, security, supply chain and customer support integrations, from the perception of the SDTs of those particular platforms. For these purposes, the analysis of current literature focusing on e-commerce software development practices has been considered to discover the typical issues of e-commerce in the interconnection with software development. A case study was conducted with a large enterprise in Sweden and in the scope of the study, a set of seven qualitative interviews were organized. The findings of the research resulted in the identification of major challenges in different aspects of e-commerce. The research also sheds light on the best practices and new insights gained by SDTs, which work collaboratively and continue to fulfil and develop new business requirements.
Keywords: software development teams; e-commerce; challenges; new hype; pandemic